Anorectal malformations in children : [electronic resources] embryology, diagnosis, surgical treatment, follow-up - 201939 Hohlschneider, Alexander M.; Hustson, John M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag, 2006)
PSZJBL